Effects of Logging Operations on Soil Physical Properties and Soil Erosion in a Hill Dipterocarp Forest of Peninsular Malaysia - Kasran, Baharuddin (1992)

(untitled)
The effects of logging operations on soil physical properties and soil erosion in logged-over forest occurred mainly on severely disturbed soil, particularly on the skid trail and logging road. Erosion plots were established i n these areas to quantify the amount of surface runoff and soil loss. Soil samples from the upper layer of the skid trail, logging road and undisturbed area were analyzed for soil physical properties. Significant changes in soil physical properties w ere observed as a result of logging operations. The bulk density increased by 32 percent on the skid trail and 42 percent on the logging road, and the total porosity reduced by 62 and 69 percent, respectively. Logging operations not only reduced the total porosity but also changed the shape and size of pores. About 82 percent of the total porosity on undisturbed area consisted of elongated pores, 18.2 percent transmission pores and 11.4 percent fissures pores. On the skid trail, the total porosity consisted of 62 percent elongated pores, 6.2 percent transmission and 4.9 percent fissures pores and on the logging road, the figures are 35, 6.4 and 2.6 percent, respectively. Thus the infiltration rate is more rapid in undisturbed forest soil than in the skid trail and logging road because it is the elongated pores that play an important role in water transmission. The higher the infiltration rate the lower is the surface runoff.